Teaching Group Counseling in Botswana: Two U.S.-Trained Counselors Discuss Experiences and Share Cultural Considerations for Practice - Coker, Angela D.; Majuta, Aaron R. (Journal for Specialists in Group Work, 2015)
There is a paucity of research in the area of teaching group counseling within an African context. In this article we describe and reflect on our experiences teaching group counseling at an institution of higher learning in the country of Botswana. We discuss cultural traditions and strengths that support an environment of group work in Botswana, describe cross-cultural challenges we experienced along the way as we implemented Western-derived didactic and experiential components of group counseling training, and discuss the ways in which we addressed the cultural differences we encountered. Implications for future cross-cultural research and training are discussed.
KerkoCite.ItemAlsoKnownAs: 10.1080/01933922.2014.992506 10/gf62j6 2129771:77YNA8B5 2317526:9N5I6ELM
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; C:Botswana; CA:AandC; CL:en; CLL:en; CLS:en; CT:A; CT:C; CT:F; CT:P; CT:Q; CT:T; F:attitude; F:learning; F:pedagogy; F:teaching; P:culture; P:environment; P:social; Q:higher education; T:Training; T:trainee; Z:Acquired Immunodeficiency Syndrome (AIDS); Z:Colleges; Z:Counselor Training; Z:Cross Cultural Training; Z:Cultural Awareness; Z:Cultural Differences; Z:Foreign Countries; Z:Group Counseling; Z:Group Dynamics; Z:Higher Education; Z:Interpersonal Communication; Z:Prosocial Behavior; Z:Social Attitudes; publicImportV1